Constitution illustrated - Sikoryak, Robert 1964- (Drawn & Quarterly, 2020)
R. Sikoryak is the master of the pop culture pastiche. In 'Masterpiece Comics', he interpreted classic literature with defining twentieth-century comics. With 'Terms and Conditions', he made the unreadable contract that everyone signs, and no one reads, readable. He employs his magic yet again to investigate the very framework of the country with 'Constitution Illustrated'. By visually interpreting the complete text of the supreme law of the land with more than a century of American pop culture icons, Sikoryak distills the very essence of the government legalese from the abstract to the tangible, the historical to the contemporary. Among Sikoryak's spot-on unions of government articles and amendments with famous comic-book characters: the Eighteenth Amendment that instituted prohibition is articulated with Homer Simpson running from Chief Wiggum; the Fourteenth Amendment that solidifies citizenship to all people born and naturalized in the United States is personified by Ms. Marvel; and, of course, the Nineteenth Amendment offering women the right to vote is a glorious depiction of Wonder Woman breaking free from her chains. American artists from George Herriman (Krazy Kat) and Charles Schulz (Peanuts) to Raina Telgemeier (Sisters) and Alison Bechdel (Dykes to Watch Out For) are homaged, with their characters reimagined in historical costumes and situations. We the People has never been more apt
Keywords: Sikoryak, Robert -- 1964-; United States -- Constitution -- Comic books, strips, etc; United States -- Constitution; USA -- The United States Constitution; Constitutional law -- United States -- Comic books, strips, etc; Constitutions -- United States -- Comic books, strips, etc; Popkultur; Staatsrecht; Comic